Mechanical and physical properties of teak leaves waste/polyurethane composites for particleboard application. (8th October 2020) - Masturi,; Jannah, WN; Maulana, RM; Darsono, T; Sunarno,; Rustad, S
A teak leaf waste/polyurethane composite has been made for particleboard application. Some fraction variations are performed on the use of polyurethane as a matrix with a range of 0.04–0.20 (w/w). Mechanical and physical properties have been tested on the composites produced. The test results showed that the highest compressive strength of the sample reaches 38.5 MPa for polyurethane fraction of 0.14 (w/w). The composite has a density of 1261 kg m −3 which is in accordance with the result of density on teak. The physical properties have been also investigated and it was found that the lowest value of water absorption is 1.38%. This result indicated that the composites produced are potentially to replace wood raw material in eco-friendly industrial scale.